Design and implementation of a decision support system Civil protection - Chellali, Mohammed Seyf Eddine; Bounif, Mohamed Elhadi: Reporter (Mohamed Boudiaf University of M'sila, 2024)
we created a data warehouse for the M'Sila Civil Protection. Which helps decision makers make the best decisions in the present and future through the daily, monthly and annual reports provided by the control panel, by exploiting the available data and using our prior knowledge to create this project.
Keywords: Design; implementation; system Civil protection; decision support